Cow bone meal applications: Changes in physicochemical properties of a degraded coarse-textured soil and cucumber performance - B Unagwu; M Igwemmadu; V Osadebe (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Degraded soils are associated with low organic matter and nutrient contents, which limit their productive capacity to produce sufficient food. Improving the productivity of degraded soils is key to achieving sustainable food production and tackling global food crises.Method: A study was carried out between September 2021 to March 2022 in a greenhouse at the University of Nigeria Nsukka Teaching and Research Farm to evaluate effect of cow bone meal (CBM) application on soil physicochemical properties and performance of cucumber grown on a degraded coarse-textured soil. The study treatments were: CBM10 (CBM at 10 t ha-1; equivalent to 22 g per 5 kg soil), CBM20 (CBM at 20 t ha-1; equivalent to 44 g per 5 kg soil), and NPK 20:10:10 fertilizer applied at recommended rate 150 kg ha-1 (0.33 g per 5 kg soil) and control.Results: CBM treatments application had remarkable positive effects on the soil physicochemical properties as well as on cucumber performance. Relative to the initial soil status, CBM application increased organic C by 139 -179%; available P by 388-396% and total N by 78-111%. Summarily, CBM20 treatment outperformed NPK fertilizer treatment on the measured soil parameters and cucumber performance, while CBM10 treatment had comparable effects with NPK treatment.Conclusion: The results obtained demonstrate the effectiveness of CBM in improving the physicochemical properties of a degraded soil. Further research work (under field conditions) is required to validate the findings of this study prior to practical implementation by end users.